DAMPAK PENERAPAN SISTEM MANAJEMEN LINGKUNGAN INTERNATIONAL ORGANIZATION FOR STANDARDIZATION (ISO) 14001:2004 TERHADAP ASPEK LINGKUNGAN, EKONOMI, DAN SOSIAL DI PT. PERKEBUNAN NUSANTARA V SEI PAGAR - Fauzi Rizky Harahap; Thamrin Thamrin; Syafruddin Nasution (Jurnal Ilmu Lingkungan, 2019)
This study is aimed to analyze the impact of the Environmental Management System of ISO 14001: 2004 to the environmental, economic, and social, analyze the effect of the environmental policy on the impact of ISO 14001: 2004, analyze the effect of the environmental planning on the impact of ISO 14001: 2004, analyze the effect of the implementation and the environmental operation on the impact of ISO 14001: 2004, analyze the effect of the examination on the impact of ISO 14001: 2004, and analyze the effect of management review of the impact of ISO 14001: 2004. The research by using a survey method with questionnaires, while the sampling technique would be used census method, in which the totals of respondents were 146 people. In analyzing the data, this study used descriptive statistical analysis method using Likert-Scale and path analysis. The findings of the study on the impact of the environmental management system of ISO 14001: 2004 showed a good result to the environmental, economic, and social. The environmental policy, environmental planning, implementation and Operation, and Examination have significant effect to the environmental, economic, and social but the management review did not significant effect to the environmental, economic, and social. Directly effected dan indirectly effected the Environmental Management with -0.63%, meanwhile, the environmental planning with4.05%, for the implementation and Operationby 6.23%.and for the examinationas well with 19.00% and then the management review with 0.03%.